The Use of a Preferential–Solvation Index (Psi) for the Comparison of Halochromic Systems - Caroli-Rezende, M; Pastenes, C (Elsevier B.V., 2021)
The study of the influence of salts on the spectral data of solvatochromic probes in solution is often a subject of difficult interpretation due to the puzzling nature of the species involved (solute, solvent, and salt). This ternary system can be understood in a similar way to the studies of binary solvent mixtures in the presence of solvatochromic dyes. Recently, a preferential–solvation index (PSI) was introduced for the study of binary solvent mixtures. The index is calculated as a ratio of two areas from a typical experimental PS plot and is not based on any theoretical model nor fitting parameters of questionable meaning. In this paper, the PSI approach was defined and used to understand salt–dependent processes in electrolyte solutions. The PSI values were calculated for fifty examples of halochromism available in the literature involving six solvatochromic probes. It was applied to systems comprising different solvents, salts, and probes, where one of these three variables was systematically varied. The values of PSI for the systems were compared with solvent (Reichardt s ET (30) and Gutmann s donor number) and cation (Klopman s softness character and ionic radii) parameters. The observed trends shed light on probe–salt and solute–solvent interactions in solution, allowing a deeper understanding of halochromic and other salt–dependent systems. © 2021 Elsevier B.V.